The Contribution of Upper Body Movements to Dynamic Balance Regulation during Challenged Locomotion - Boström, Kim J.; Dirksen, Tim; Zentgraf, Karen; Wagner, Heiko (Frontiers in Human Neuroscience, 2018)
Recent studies suggest that in addition to movements between ankle and hip joints, movements of the upper body, in particular of the arms, also significantly contribute to postural control. In line with these suggestions, we analyzed regulatory movements of upper and lower body joints supporting dynamic balance regulation during challenged locomotion. The participants walked over three beams of varying width and under three different verbally conveyed restrictions of arm posture, to control the potential influence of arm movements on the performance: The participants walked 1) with their arms stretched out perpendicularly in the frontal plane, 2) spontaneously, i.e., without restrictions to the arm movements, and 3) with their hands on their thighs. After applying an inverse-dynamics analysis to the measured joint kinematics, we investigated the contribution of upper and lower body joints to balance regulation in terms of torque amplitude and variation. On the condition with the hands on the thighs, the contribution of the upper body remains significantly lower than the contribution of the lower body irrespective of beam widths. For spontaneous arm movements and for outstretched arms we find that the upper body (including the arms) contributes to the balancing to a similar extent as the lower body. Moreover, when the task becomes more difficult, i.e., for narrower beam widths, the contribution of the upper body increases, while the contribution of the lower body remains nearly constant. These findings lend further support to the hypothetical existence of an ``upper body strategy'' complementing the ankle and hip strategies especially during challenging dynamic balance tasks.